Computational archaeology of the Pristionchus pacificus genome reveals evidence of horizontal gene transfers from insects - Rödelsperger, Christian (BioMed Central, 2011)
BACKGROUND: The recent sequencing of nematode genomes has laid the basis for comparative genomics approaches to study the impact of horizontal gene transfer (HGT) on the adaptation to new environments and the evolution of parasitism. In the beetle associated nematode Pristionchus pacificus HGT events were found to involve cellulase genes of microbial origin and Diapausin genes that are known from beetles, but not from other nematodes. The insect-to-nematode horizontal transfer is of special interest given that P. pacificus shows a tight association with insects. RESULTS: In this study we utilized the observation that horizontally transferred genes often exhibit codon usage patterns more similar to that of the donor than that of the acceptor genome. We introduced GC-normalized relative codon frequencies as a measure to detect characteristic features of P. pacificus orphan genes that show no homology to other nematode genes. We found that atypical codon usage is particularly prevalent in P. pacificus orphans. By comparing codon usage profiles of 71 species, we detected the most significant enrichment in insect-like codon usage profiles. In cross-species comparisons, we identified 509 HGT candidates that show a significantly higher similarity to insect-like profiles than genes with nematode homologs. The most abundant gene family among these genes are non-LTR retrotransposons. Speculating that retrotransposons might have served as carriers of foreign genetic material, we found a significant local clustering tendency of orphan genes in the vicinity of retrotransposons. CONCLUSIONS: Our study combined codon usage bias, phylogenetic analysis, and genomic colocalization into a general picture of the computational archaeology of the P. pacificus genome and suggests that a substantial fraction of the gene repertoire is of insect origin. We propose that the Pristionchus-beetle association has facilitated HGT and discuss potential vectors of these events.